DOI: 10.4018/978-1-4666-8662-5.ch009
|View full text |Cite
|
Sign up to set email alerts
|

A Tutorial on Network Latency and Its Measurements

Abstract: Internet latency is crucial in providing reliable and efficient networked services when servers are placed in geographically diverse locations. The trend of mobile, cloud, and distributed computing accelerates the importance of accurate latency measurement due to its nature of rapidly changing locations and interactivity. Accurately measuring latency, however, is not easy due to lack of testing resources, the sheer volume of collected data points, the tedious and repetitive aspect of measurement practice, cloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The data, when presented in the form of a histogram, looked like a lognormal distribution. However, literature 12,13 suggested that network latency data may align with either a lognormal, Weibull, Rayleigh, or Gamma distribution. Analysis, as seen in Figure 5, revealed that these data were best fit to a lognormal distribution with a mu parameter of 6.0075 and a sigma parameter of 0.54912.…”
Section: In-situ Demonstration Resultsmentioning
confidence: 96%
“…The data, when presented in the form of a histogram, looked like a lognormal distribution. However, literature 12,13 suggested that network latency data may align with either a lognormal, Weibull, Rayleigh, or Gamma distribution. Analysis, as seen in Figure 5, revealed that these data were best fit to a lognormal distribution with a mu parameter of 6.0075 and a sigma parameter of 0.54912.…”
Section: In-situ Demonstration Resultsmentioning
confidence: 96%
“…We define a third metric, Υ, that determines how much data is being transmitted across the WAN during computations [38], [39]. Some cloud operators (e.g., AWS [37]) only charge for outgoing traffic, not for the incoming traffic.…”
Section: Evaluation Criteriamentioning
confidence: 99%
“…Ishii et al [30] conduct experiments on AWS [1] using a parallel Data Processing Application and observe processing time between 400 and 1800 ms. Lee et al [37] and Claypool et al [16] observe drop in user experience when playing computer games with artificially increased latency to larger than 200 ms. In summary, we focus on applications with long processing times, 10 ms -1 s, and on average internet round trip times, 60-600 ms [36].…”
Section: Challenges In Distributed Cloudsmentioning
confidence: 99%